Analysis of Test Results for Coffee Peeler Machine with a Capacity of 40 Kg/Hour - Nofan Miranza (International Journal of Mechanical Computational and Manufacturing Research, 2022)
During the long-term development until now, industrial machinery products have shown very rapid progress, both in terms of volume and variety of products produced. The development of this product is not only marked by the fulfillment of the interests of the community, but also leads to the ability to enter exports to increase the country's foreign exchange. reference books, literature complements the theories in this report. (2) The method of consultation, with the final project supervisor, as well as the workshop person where the author completed this design. (3) Conducting field surveys, by viewing and comparing existing appropriate technology machines. The main components of the coffee peeling machine analyzed include: - Motor power - Belt (V-belt) - Shaft - Bearing - Peeler Capacity From several tests that have been carried out, the following conclusions can be drawn: (1) The production speed of the tool is 60 minutes with tool efficiency 93%. (2) The rotational speed used is 478 rpm (3) The planned load capacity is 40 kg (4) The driving motor power Hp. (5) The transmission system used is belt and pulley. There are several factors that cause coffee cherries to not be peeled by the peeler, including: - Young (green) coffee cherries - Irregular shape - Sleeping paring teeth - The distance between the peeler teeth and the bruising plate is far apart. Suggestions in this research are: (1) It is better to take care of the components of this tool because it is easy to corrode. (2) Check the tool before operation.